The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/20499361211009385
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and post-infectious myalgic encephalomyelitis/chronic fatigue syndrome: a narrative review

Abstract: Coronavirus disease 2019 (COVID-19) is a viral infection which can cause a variety of respiratory, gastrointestinal, and vascular symptoms. The acute illness phase generally lasts no more than 2–3 weeks. However, there is increasing evidence that a proportion of COVID-19 patients experience a prolonged convalescence and continue to have symptoms lasting several months after the initial infection. A variety of chronic symptoms have been reported including fatigue, dyspnea, myalgia, exercise intolerance, sleep d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
105
0
10

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(143 citation statements)
references
References 135 publications
4
105
0
10
Order By: Relevance
“…There are no specific biomarkers, and diagnosis is typically based on symptoms. In fact, a subset of patients suffering from COVID-19 satisfied the diagnostic criteria of CFS/ME [ 7 ] In addition, major post-acute COVID-19 symptoms resemble post-infectious ME/CFS [ 8 ]. The changes in neurotransmitter levels, inflammation, psychological disorders, stress levels, and cognitive dysfunction are thought to be contributing factors in fatigue [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are no specific biomarkers, and diagnosis is typically based on symptoms. In fact, a subset of patients suffering from COVID-19 satisfied the diagnostic criteria of CFS/ME [ 7 ] In addition, major post-acute COVID-19 symptoms resemble post-infectious ME/CFS [ 8 ]. The changes in neurotransmitter levels, inflammation, psychological disorders, stress levels, and cognitive dysfunction are thought to be contributing factors in fatigue [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the deficient development of various eccrine glands in HED patients entails recurrent respiratory infections, atrophic rhinitis, and keratoconjunctivitis sicca [6,16], neither the course of COVID- observed concerning postinfectious fatigue, a chronic illness with constitutional and neurocognitive symptoms persisting long after clearance of the initial infection [17]. Chronic fatigue is a multifactorial and poorly understood consequence of a variety of predominantly viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic fatigue is a multifactorial and poorly understood consequence of a variety of predominantly viral infections. Coxiella burnetii, Epstein-Barr virus, influenza virus, and other infectious agents have been hypothesized to cause persistent dysregulation of inflammatory response and metabolic pathways, most likely related to a miscommunication in cytokine networks [17,18]. There is an increasing number of individuals who suffer from post-acute COVID-19, an even more complex disease entity characterized by persistent symptoms and/or delayed or long-term complications beyond 4 weeks from the onset of symptoms [19,20], including anosmia, muscular weakness, cognitive and sleep disturbances, chest pain, palpitations, and hair loss.…”
Section: Discussionmentioning
confidence: 99%
“…A review of the neurologic impact of COVID-19 identified two major categories: 1) acute and rarely occurring severe consequences such as Guillain-Barré syndrome or encephalitis, and 2) chronic, highly variable, and often time-varying symptoms which overlap with conditions such as myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). 15 Symptoms such as dyspnea, myalgia (muscle pain), exercise intolerance and sleep disturbances that are commonly reported in the post COVID-19 condition have some similarities to symptom complexes noted in ME/CFS. 15 Fatigue is one of the most commonly reported cognitive symptoms by individuals with the post COVID-19 condition, and was reported by 40% of individuals post infection with influenza or coronaviruses such as severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS).…”
Section: Neurologic Dysfunctionmentioning
confidence: 97%
“…15 Symptoms such as dyspnea, myalgia (muscle pain), exercise intolerance and sleep disturbances that are commonly reported in the post COVID-19 condition have some similarities to symptom complexes noted in ME/CFS. 15 Fatigue is one of the most commonly reported cognitive symptoms by individuals with the post COVID-19 condition, and was reported by 40% of individuals post infection with influenza or coronaviruses such as severe acute respiratory syndrome (SARS) and Middle East respiratory syndrome (MERS). 16 Persistent post-viral fatigue beyond 6 months was noted post SARS infection in approximately one quarter of patients.…”
Section: Neurologic Dysfunctionmentioning
confidence: 97%